A 5-year retrospective review of fungal keratitis at Hospital Universiti Sains Malaysia - Mohd Tahir, Fadzillah; A., Norhayati; Ishak, Siti Raihan; M., Ibrahim (Hindawi Publishing Corporation, 2012)
Corneal blindness from healed infected keratitis is one of the most preventable causes of monocular blindness in developing countries, including Malaysia. Our objectives were to identify the causative fungi, predisposing risk factors, the proportion of correct clinical diagnosis, and visual outcome of patients treated in our hospital. Methods. A retrospective review of medical and microbiology records was conducted for all patients who were treated for fungal keratitis at Hospital Universiti Sains Malaysia from January 2007 until December 2011. Results. Forty-seven patients (47/186, 25.27%) were treated for fungal keratitis during the study period. This demonstrated that the incidence of fungal keratitis has increased each year from 2007 to 2011 by 12.50%, 17.65%, 21.21%, 26.83%, and 28.57%, respectively. The most common predisposing factors were injury to the eye followed by use of topical steroid, and preexisting ocular surface disease. Fusarium species were the most common fungal isolated, followed by Candida species. Clinical diagnosis of fungal keratitis was made in 26 of the 41 (63.41%) cases of positive isolates. Of these, in eleven cases (23.40%) patients required surgical intervention. Clinical outcome of healed scar was achieved in 34 (72.34%) cases. Conclusions. The percentage of positive fungal isolated has steadily increased and the trend of common fungal isolated has changed. The latest review regarding fungal keratitis is important for us to improve patients’ outcome in the future.